CONSOLIDATION CHARACTERISTICS UNDER CYLINDER TEST, CENTRIFUGAL TEST AND OEDOMETER TEST - Rondonuwu, Steeva G.; Sarajar, Alva N. (TEKNO, 2016)
A several laboratory tests have conducted to investigate the self-weight consolidation characteristics on Ariake washed. They are self weight consolidation by cylinder test and centrifuge test, while incremental loading by oedometer test as well. All the samples were used have passed through a 425 Î¼m siever to remove the granular particles. For cylinder test series, we adjust the suspension for each sample in initial water content range from 103 % to 1000 %, corresponding to liquid limit start from 1. Then let the self-weight consolidation process occurred. After the final process, we measured the final water content and maximum settling rate. Next for centrifugal test, we adjust the sample in liquidity index (IL) equal 1.5. The initial height specimens were 6, 4, 2, and 1 cm. All the specimens were played in centrifuge device. For 5 and 6 cm initial height specimen we adjust the velocity 850 rpm, and 800 rpm for 1 and 2 cm initial height specimen. The settling was recorded on elapsed time ranging from 15 to 1440 minute randomly. As for oedometer test, we adjusted the samples under 0.75, 1.0, 1.25, and 1.0 in liquidity index. Key words: self weight consolidation, settlement, centrifuge, sediment